Green innovations and export performance - Stefano Meneto; Iulia Siedschlag (The Economic and Social Research Institute (ESRI), 2020)
This paper examines the relationship between innovations with environmental benefits (green innovations) and firms' export performance. Using firm-level data from Ireland's Community Innovation Survey over 2012-2014, we examine whether and to what extent green innovations are associated with firms' export participation and with the intensity of their exports. Our estimates indicate that innovations with environmental benefits for the consumer and product innovations with environmental benefits were positively associated with firms' export participation. Further, our results indicate that green innovations do not appear to impact on how much firms export. Taken together, our results suggest that environmental policy-induced innovations could be beneficial for the international competitiveness of firms measured as export participation.
Keywords: F14; O33; Q56; 330; Environmental policy; green innovations; export performance